Balancing Legal Certainty and Substantive Justice in Indonesian Bankruptcy Law: Simple Proof, Judicial Responsibility, and Curator Accountability - Pradipta, Mochammad Deanasti; Soekarini, Noenik; Ayuningtyas, Fitri (Jurnal Ragam Pengabdian, 2026)
Indonesia’s Law Number 37 of 2004 was designed to provide a rapid, simple, and collective mechanism for resolving unpaid debts. Nevertheless, the combination of a low statutory threshold for bankruptcy and the open-textured requirement of “simple proof” continues to generate tension between legal certainty and substantive justice. This article examines how those principles are regulated and applied, and evaluates the responsibilities of commercial judges and curators in protecting creditors and debtors. The study uses normative legal research with statutory, conceptual, and case approaches. Primary materials comprise bankruptcy legislation, judicial-power rules, selected Constitutional Court and Supreme Court materials, and relevant commercial-court reasoning; secondary materials consist mainly of recent peer-reviewed legal scholarship. The analysis finds that certainty is weakened not by the absence of procedural rules, but by the lack of operational standards for disputed debt, maturity, creditor plurality, proportionality, and financial distress. Justice is also vulnerable after adjudication when estate administration is insufficiently transparent or effectively supervised. The article proposes a two-stage judicial screening model, a structured proportionality test, clearer statutory indicators of simple proof, and digital, periodic curator reporting. These reforms would preserve procedural speed while reducing strategic petitions and strengthening balanced protection for all parties.